Changes in vegetation seasonality and livestock stocking rate in La Pampa Province (Argentina) - Di Bella, Carlos Marcelo (2019)
Fil: Di Bella, Carlos Marcelo. Instituto Nacional de Tecnología Agropecuaria (INTA). Instituto de Suelos (INTA-CIRN). Hurlingham, Buenos Aires, Argentina.